Responsibility of Tin Mining Business Licenses for Environmental Pollution Based on the Polluter Pays Principle - Sri Rahayu; Bunga Permatasari; Winanda Kusuma (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2023)
The purpose of writing this article is to find out and analyze the polluter pays principle concept and its regulations in Indonesia, as well as to find out and analyze the accountability of tin mining business permits for environmental pollution based on the polluter pays principle. Therefore the research method used in this article uses a normative juridical method with a conceptual approach and statutory approach. The article reveals that PPP in Indonesia involves both preventive and repressive measures to address environmental pollution. Polluters are charged with compensation, but regulations like UUPPLH and Minerba Law are more repressive. Implementation involves guarantee, pollution, and conservation funds, funded by APBN/APBD grants/donations. PT. Timah, as the largest tin IUP holder in Babel, has carried out 100% reclamation, but overall, of the total IUP holders in Babel, these funds are apparently not commensurate with the damage that arises as a result of tin mining exploitation activities. And the number of newly reclaimed areas is 1.59% of the total IUP that has been granted. And the form of civil liability is regulated in the UUPPLH, while criminal liability is regulated in the Minerba Law.